A systematic review on the biochemical threshold of mitochondrial genetic variants - Smith, Karan K.; Moreira, Jesse D.; Wilson, Callum R.; Padera, June O.; Lamason, Ashlee N.; Xue, Liying; Gopal, Deepa M.; Flynn, David B.; Fetterman, Jessica L. (Genome Research, 2024)
Mitochondrial DNA (mtDNA) variants cause a range of diseases from severe pediatric syndromes to aging-related conditions. The percentage of mtDNA copies carrying a pathogenic variant, variant allele frequency (VAF), must reach a threshold before a biochemical defect occurs, termed the biochemical threshold. Whether the often-cited biochemical threshold of >60% VAF is similar across mtDNA variants and cell types is unclear. In our systematic review, we sought to identify the biochemical threshold of mtDNA variants in relation to VAF by human tissue/cell type. We used controlled vocabulary terms to identify articles measuring oxidative phosphorylation (OXPHOS) complex activities in relation to VAF. We identified 76 eligible publications, describing 69, 12, 16, and 49 cases for complexes I, III, IV, and V, respectively. Few studies evaluated OXPHOS activities in diverse tissue types, likely reflective of clinical access. A number of cases with similar VAFs for the same pathogenic variant had varying degrees of residual activity of the affected complex, alluding to the presence of modifying variants. Tissues and cells with VAFs <60% associated with low complex activities were described, suggesting the possibility of a biochemical threshold of <60%. Using Kendall rank correlation tests, the VAF of the m.8993T > G variant correlated with complex V activity in skeletal muscle (τ = −0.58, P = 0.01, n = 13); however, no correlation was observed in fibroblasts (P = 0.7, n = 9). Our systematic review highlights the need to investigate the biochemical threshold over a wider range of VAFs in disease-relevant cell types to better define the biochemical threshold for specific mtDNA variants.